2022
DOI: 10.1111/jdv.18378
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severity of atopic dermatitis – a Finnish cross‐sectional study

Abstract: Background Severity‐associated factors in atopic dermatitis (AD) have focussed on early onset, concomitant atopic diseases, markers of Th2‐shifted inflammation and filaggrin mutations. Objectives To investigate factors associated with severe AD in Finnish patients. Methods We conducted a single‐centre, cross‐sectional observational study with 502 AD patients aged 4.79 to 79.90 years (mean 32.08 years). Disease severity was assessed with the Rajka–Langeland severity score and EASI and associated clinical signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Overall, patients with severe AD and systemic medication were found older, more often male, and with lower educational level than those without systemic medication. Previously, male gender was shown to be a risk factor for more severe AD and male AD patients were suggested to have a lower tendency to seek healthcare services 21 . In our study, systemically treated patients were detected with more cases of sepsis after initiation of systemic therapy, which may indicate increased susceptibility for severe infections in this patient group.…”
Section: Discussionsupporting
confidence: 49%
“…Overall, patients with severe AD and systemic medication were found older, more often male, and with lower educational level than those without systemic medication. Previously, male gender was shown to be a risk factor for more severe AD and male AD patients were suggested to have a lower tendency to seek healthcare services 21 . In our study, systemically treated patients were detected with more cases of sepsis after initiation of systemic therapy, which may indicate increased susceptibility for severe infections in this patient group.…”
Section: Discussionsupporting
confidence: 49%
“…20 BMI is higher in patients with severe AD than in those with mild AD. 22 In children aged >2 years, BMI > 24 is positively correlated with AD severity scores. 49 Similar results were also observed in a group of patients aged 1-46 years.…”
Section: The Link B E T Ween Ad With Ob E S It Ymentioning
confidence: 99%
“…The association of AD with obesity has been fairly well documented, although the conclusions among studies are not consistent (Table 1). 12,19–64 In children, prevalence of obesity is significantly higher in individuals with AD than in those without AD 24 . Also in children, the presence of AD/eczema is positively associated with obesity, while negatively associated with underweight subjects 30 .…”
Section: The Link Between Ad With Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Finnish study showed that early disease onset, male gender and comorbid asthma were determinants of AD severity. 5 It is unknown why men seem to have more severe disease, but low topical treatment adherence or healthcare consumption could explain it. 6 Also, results suggest that women are more adherent to topical treatments and maybe less prone to accept the potential side-effects of systemic medication.…”
mentioning
confidence: 99%